RELIGIOUS MODERATION IN THE RECITATION ACTIVITY OF MUSLIMAT NU: An Effort to Prevent Religious Extremism - Rohmawati, Yuyun; Barizi, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2021)
The lives of religious people are often in the spotlight because of complex problems. Religion which is supposed to be the source of peace, causes chaos. Hence, the moderation values must be taught in religious life to create peace. This study aims to explain the efforts and contribution of Muslimat NU Durek Hamlet, Batu City in internalizing the religious moderation values to prevent religious extremism. This is a qualitative research with a case study approach. The data are collected using observation, interviews, and documentation. The analysis technique includes data condensation, data display, conclusion drawing and verifying. The data are then verified using triangulation techniques. The results reveal that there are three efforts done by the Muslimat NU Durek Hamlet to internalize the religious moderation, namely oral method, exemplary, and monitoring. The values taught are balance, tolerance, deliberations, good prejudice and fair. Meanwhile, the contribution of religious moderation in preventing religious extremism is tolerance for differences, being friendly, polite, and doing deliberation.